Bridging the Second-Level Digital Divide: Prioritizing Emotional and Social Literacy through Intergenerational Communication in Rural China - Liu, Qian; Wang, Qing; Park, Chang Sup (International Journal of Mass Communication, 2026)
Based on interviews with 52 Xianchong Village residents, this study shows older adults value emotional comfort, relational ties, and family support in digital inclusion. Rather than technical skills alone, seniors emphasize well-being and social cohesion when using technology. Intergenerational communication—especially reciprocal family learning—reduces digital alienation, reflecting Confucian ideals of filial piety and responsibility, especially in rural contexts dominated by family networks. While some barriers resemble first-level divides, findings mainly address second-level dynamics, highlighting emotional and social aspects of digital literacy. Mechanisms such as reassurance, cultural continuity, and reciprocity persist across technological shifts, reframing digital inequality as relational and affective, and revealing how enduring cultural norms shape engagement.